The importance of interim measures for the development of international commercial arbitration as an independent method of dispute resolution - Prykhodko, Anna Volodymyrivna (My University, 2016)
The article provides an overview of the importance of further developing and enforcing interim measures in international commercial arbitration proceedings. The conclusion is drawn about the need to consider interim measures as a “stand-alone” solution. У статті наведено огляд важливості подальшого розвитку та забезпечення виконання тимчасових заходів у процедурах міжнародного комерційного арбітражу. Зроблено висновок про необхідність розглядати тимчасові заходи як «окреме» рішення.
Keywords: international commercial arbitration; міжнародний комерційний арбітраж; dispute resolution; вирішення спорів